44. CURRENT STATUS OF ICD-10 DISEASE CODING IN INPATIENT MEDICAL RECORDS AT THE HOSPITAL OF POST AND TELECOMMUNICATIONS (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the current status of ICD-10 disease coding in inpatient medical records and assess the knowledge of healthcare workers, as well as analyze associated factors at the Hospital of Post and Telecommunications in 2024.Methods: A cross-sectional descriptive study was conducted from December 2024 to March 2025 at the Hospital of Post and Telecommunications. A total of 420 inpatient medical records were selected via systematic random sampling, and 98 healthcare workers were surveyed using a self-administered questionnaire.Results: Only 32.6% of primary diagnoses were coded using four-character ICD-10 codes, while the majority (67.4%) used three-character codes. Comorbidities were recorded in 24.8% of cases, of which 95.2% were coded completely, and 55.8% utilized a combination of three- and four-character codes. Regarding ICD-10 knowledge, 75.5% of healthcare workers met the minimum knowledge requirement, but only 41.8% understood the character structure rule. Factors significantly associated with sufficient ICD-10 knowledge included postgraduate education, ≥ 10 years of experience, and having received ICD-10 training.Conclusions: ICD-10 disease coding at the Hospital of Post and Telecommunications remains limited in detail and accuracy, primarily due to human factors and lack of structured training. It is essential to conduct regular training, implement standardized coding procedures, assign dedicated coding personnel, and invest in supportive digital tools to improve medical record management and health insurance reimbursement.
Keywords: ICD-10; disease coding; medical records; hospital; healthcare workers